Economic cooperation and environmental sustainability in the OIC region: a panel data analysis - Thalut, Nashipu; Mat Ghani, Gairuzazmi (2025)
Regional economic cooperation is one of the important components of trade policy. Understanding its effect on environmental sustainability is essential for eco-friendly economic cooperation. This study investigates the effects of economic cooperation on environmental sustainability in the Organisation of Islamic Cooperation (OIC) region using panel data spanning over the period of 11 years from 2010 to 2020. To understand the effects of economic cooperation on environmental sustainability, the paper employed preferential trade agreements (PTA), economic union (EU), institutional-driven integration (IDI) and pooled regional integration (REI) as indicators of economic cooperation while ecological footprint was used to capture environmental sustainability. The paper employed Tobit panel censored regression and Driscoll-Kraay standard errors regression model to document the nexus between economic cooperation and environmental sustainability in the OIC region. The results indicated that regional economic integration, preferential trade agreements, economic union, and institutional driven integration reduces ecological footprint of OIC member countries. The results also indicated that foreign direct investment net inflows can improve the environmental sustainability of OIC regional bloc members. Based on the findings, it is recommended that OIC member countries should strengthen environmental policies as they deepened regional economic cooperation.